Pre and Spread Covid-19 of Market and Financial Performance On Transportation Companies - Kadarningsih, Ana; Safitri, Maria; Oktavia, Vicky (Pustaka Galeri Mandiri, 2022)
This research is intended to examine the extent to which financial performance and market performance encourage financial stability in the long term, especially during the pandemic for 50 transportation companies in Indonesia. The purpose of this study focuses on measuring the financial performance of 2 ratios, namely the Retun On Asset and Debt Equity Ratio, and market performance as measured by Price Earning Ratio and Price Book Value, before and during the pandemic. This research is quantitative. by using secondary data. The sampling used in this study was purposive sampling, with a sample of 50 transportation companies listed on the IDX from 2018 to 2021 with a total of 600 data. Hypothesis testing in this study used a non-parametric test, namely the Wilcoxon-signed rank test to analyze the difference in the mean of two related variables. This test is to see differences in the financial and market performance of transportation companies before and during the covid-19 pandemic in Indonesia. The data processing in this study uses SPSS version 26. The Wilcoxon Signed Rank results show that there are differences in PER, PBV and ROA were significant before and during the COVID-19 pandemic, while there was no difference in DER.